2020
DOI: 10.3758/s13428-020-01483-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attention and vigilance in the laboratory vs. online: The split-half reliability of the ANTI-Vea

Abstract: Over the past few years, there has been growing interest in using online methods for collecting data from large samples. However, only a few studies have administered online behavioral tasks to assess attention outside the lab. In the present study, we assessed the classic attentional functions and two vigilance components using two versions of the Attentional Networks Test for Interactions and Vigilance-executive and arousal vigilance components (ANTI-Vea): (1) a standard version, performed under typical expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 70 publications
(173 reference statements)
6
44
3
3
Order By: Relevance
“…Besides the sampling bias discussed above, a more plausible reason is related to the psychometric properties of the ANTI-Vea indexes. Although our task reliability scores are similar to the ones reported in Luna, Roca, et al (2020), the reliability found for difference scores and slopes tended to be fairly low. This limitation, which is also inherent to most cognitive tasks (Dang, King, & Inzlicht, 2020;Hedge, Powell, & Sumner, 2018), could dramatically attenuate the observed correlations coefficients.…”
Section: Limitationssupporting
confidence: 76%
See 3 more Smart Citations
“…Besides the sampling bias discussed above, a more plausible reason is related to the psychometric properties of the ANTI-Vea indexes. Although our task reliability scores are similar to the ones reported in Luna, Roca, et al (2020), the reliability found for difference scores and slopes tended to be fairly low. This limitation, which is also inherent to most cognitive tasks (Dang, King, & Inzlicht, 2020;Hedge, Powell, & Sumner, 2018), could dramatically attenuate the observed correlations coefficients.…”
Section: Limitationssupporting
confidence: 76%
“…Although a loss of sensitivity over the task has been reported in our data as well as in studies with high statistical power(Feltmate et al, 2020;Luna, Roca, et al, 2020), this effect size seems to be lower than the effect on the response criterion.…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…Notwithstanding, Thomson et al outcomes were replicated later in a study conducted under the typical lab conditions (Claypoole et al, 2018). Indeed, we have recently analyzed the reliability of the vigilance and attentional components of the ANTI-Vea in a study with a large sample (N = 617), wherein participants either performed the standard ANTI-Vea in the lab or the online version (https://www.ugr.es/~neurocog/ANTI/) outside the lab in a suitable place of their choosing (Luna, Roca, Martín-Arévalo, & Lupiáñez, 2020). In short, we observed that in both task versions, the split-half reliability indices (corrected by the Spearman-Brown prophecy) were higher than .75 for both the EV and AV measures.…”
Section: Discussionmentioning
confidence: 99%